DETERMINAN BELANJA ONLINE MENGGUNAKAN APLIKASI TOKOPEDIA PADA MAHASISWA UNIVERSITAS UDAYANA - Bunga Lestari, Nuraqni Dwi; Kt. Gd. Suasana, I Gst. A. (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2024)
The increasingly rapid development of technology is driving changes in the behavior of today's people who are increasingly fond of shopping online through e-commerce. The aim of this research is to determine the influence of perceived convenience and perceived usefulness on decisions to use the Tokopedia application which is mediated by trust. This research was conducted on Udayana University students with a total sample of 105 samples determined using a non-probability sampling method with purposive sampling technique. The Partial Least Square (PLS) method was used to test the data. The research results show that perceived convenience has a positive but not significant effect on the decision to use, perceived usefulness and trust has a positive and significant effect on the decision to use, perceived ease and perceived usefulness has a positive and significant effect on trust. Theoretically, the results of this research support previous research and can also add to empirical studies. Practically, the research results can be used by companies to evaluate their application services by paying attention to user behavior patterns in terms of perceived convenience and perceived benefits which can foster trust so that they can increase Tokopedia application users.